Spontaneous uterine rupture in first trimester of pregnancy - Sinha, Parul; Agrawal, Nisha Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is a case of 30 years old female who presented in emergency at 11 weeks 3 days with acute abdomen and diagnosed as spontaneous uterine rupture. The defect was repaired and bilateral tubal ligation was done. This shows that uterine rupture can occur as early as that late first trimester and should be included in the differential diagnoses of acute abdomen.